2020
DOI: 10.1557/mrc.2020.76
|View full text |Cite
|
Sign up to set email alerts
|

Relating nanoscale structure to optoelectronic functionality in multiphase donor–acceptor nanoparticles for printed electronics applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Optically, the nanoparticle active layer exhibits light absorption relatively similar to Bulk heterojunction (BHJ) active layer. As the results of optical modelling confirmed that the optimum Jsc of NPs compared with BHJ has no more two magnitude values [8], However, the problem of NPs device is the charge transfer (charge Mobility) in active layer due to the boundaries of NPs in comparison to BHJ structure that has non-structural between donor/acceptor, a free charge has high probability to cross active layer and collected out the BHJ device [14]. In general optical modeling here is utilized to give an idea of the optimum performance of the OPV -device before laboratory preparation relying on UV-vis measurements for active layer thin film.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Optically, the nanoparticle active layer exhibits light absorption relatively similar to Bulk heterojunction (BHJ) active layer. As the results of optical modelling confirmed that the optimum Jsc of NPs compared with BHJ has no more two magnitude values [8], However, the problem of NPs device is the charge transfer (charge Mobility) in active layer due to the boundaries of NPs in comparison to BHJ structure that has non-structural between donor/acceptor, a free charge has high probability to cross active layer and collected out the BHJ device [14]. In general optical modeling here is utilized to give an idea of the optimum performance of the OPV -device before laboratory preparation relying on UV-vis measurements for active layer thin film.…”
Section: Resultsmentioning
confidence: 67%
“…The nanoparticle organic photovoltaics (NP-OPVs) offered a water processability concept of active layer material and then eliminating harm solvents [7,8], with the ability to control the semi-conducting polymer in addition to preparing nanoscale morphology [9,10]. Thus, the nanoparticle organic photovoltaics (NP-OPVs) have contributed in reduction the environmental, health, and safety issues in fabrication process of NPs devices, compared to conventional bulk heterojunction (BHJ) devices [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Sydney, Matthew Griffith Nanomaterial synthesis (organic and composite blends) by miniemulsion ultrasonification ARC [ 139,[216][217][218] NHMRC UWA, Paul Low, George Koutsantonis Small molecule synthesis, conjugated carbon-rich molecules and materials, organic and organometallic compounds and complexes, anchor groups and strategies ARC [ 102,[219][220][221][222] Various www.publish.csiro.au/ch Australian Journal of Chemistry time-resolved measurements, single-photon measurements, and various microscopies and imaging methods. Significant capabilities of particular relevance to aspects of molecular electronics research are identified in Curtin, Macquarie, Melbourne, Monash, UNSW and UWA.…”
Section: Referencesmentioning
confidence: 99%
“…105 More recently, Al-Mudhaffer et al reported that the core-shell morphology can be modulated by using active materials with higher miscibilities, such as P3HT: indene C60bisadduct (ICBA). 106 Pan et al observed higher PL intensities using o-xylene as an organic solvent for the preparation of nanoparticles through miniemulsion, in comparison to dispersions using chloroform as an organic solvent. They concluded that the use of o-xylene led to the formation of more segregated domains within the nanoparticle.…”
Section: Influence Of the Techniquementioning
confidence: 99%
“…The morphology of PSBTBT:PC 61 BM and P3HT:PC 61 BM nanoparticles was then measured by STXM and confirmed to be core–shell, with a polymer-rich shell . More recently, Al-Mudhaffer et al reported that the core–shell morphology can be modulated using active materials with higher miscibilities, such as P3HT:indene C 60 bisadduct (ICBA) …”
Section: Nanoparticle Structurementioning
confidence: 99%